Healthcare information technology innovation and sustainability : frontiers and adoption - Tan, Joseph K. H. (Hershey PA : Medical Information Science Reference)
"This book presents research in the emerging field on information systems and informatics in the healthcare industry, addressing innovative concepts and critical issues through case studies and experimental research"--Provided by publisher